Respuesta :

Answer:

The 4th option is correct.

The equation of the line is: (y + 3) = 3 (x - 4)

Step-by-step explanation:

The equation of a line using two points, (x₁, y₁) and (x₂, y₂) is:

[tex](y-y_{1})=m(x-x_{1})[/tex]

Here m is the slope of the line.

The formula to compute slope is:

[tex]m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex]

Given: The two points are (4, -3) and (5, 0)

The equation of the line passing through the points (4, -3) and (5, 0) is:

[tex](y-y_{1})=m(x-x_{1})\\(y-y_{1})=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}(x-x_{1})\\(y-(-3))=\frac{0-(-3)}{5-4}(x-4)\\(y+3)=3(x-4)[/tex]

Thus, the line passing through the points (4, -3) and (5, 0) is (y + 3) = 3 (x - 4).

The one above is correct